Performance of steers limit-fed in drylot or on mature native pasture - Brazle, F.K.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Growing steers were limit-fed the same amount of a grain- and silage-based ration either in drylot or on dormant native range. The steers wintered on pasture gained 14.2% slower (1.82 V5 2.08 lb/d; P<.01) and were 15.3% less efficient than those in drylot, apparently because of increased energy expenditure from voluntary exercise.
Keywords: Beef; Mature grass; Drylot; Growing; Limit feeding